STUDI CEMARAN MIKROBA PADA RENDANG SAPI DI RUMAH MAKAN PADANG DI KECAMATAN KUTA, KABUPATEN BADUNG, BALI - Sembiring, Sixtian Brema; Putra, I Nengah Kencana; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i01.p09, 2019)
The purpose of this study was to determine the microbial contamination on beef rendang and hygiene sanitation practices at Padang restaurant in Kuta sub district, Badung regency , Bali. This study used survey method with purposive sampling technique. The sampling determination was conducted at several Padang restaurants in Kuta sub district , Badung regency, Bali . The data obtained were presented in the form of tables, pictures, and analyzed descriptively. The variable observed were total microbes, Escherichia coli, and Staphylococcous aureus. The results showed that 90% of beef rendang was suitable with requirements of total microbes for processed meat in Indonesia ( SNI< 5 x 10 5 ), 80% of beef rendang was suitable with requirements of Escherichia coli for processed meat in Indonesia and 100% of beef rendang was suitable with requirements of Staphylococcous aureus for processed meat in Indonesia. The amount of 90% of beef rendang was cooked in the morning, 20% of rendang was served over 24 hours. The hygiene and sanitation practices at Padang restaurant in Kuta subdistrict, Badung regency were good enough .